Beyond carbon: Quantifying environmental externalities as energy for hydroelectric and nuclear power. (1st May 2015) - Sheldon, Seth; Hadian, Saeed; Zik, Ory
Abstract: Together, hydroelectric and nuclear power account for roughly 30% of all electricity generated on earth. Both technologies are often presented as answers to the dual challenge of meeting ever-increasing global energy demand while meeting stricter GHG (greenhouse gas) emissions targets. Indeed, the last two decades have witnessed a great deal of research on the life cycle GHG emissions of these technologies. On the basis of carbon intensity, the general consensus is that these technologies are more efficient than all other technologies of similar scale (e.g. coal, natural gas). However, hydroelectric and nuclear power come with environmental costs that sit outside the boundaries of traditional energy-based accounting methods, including water consumption, land change, and waste generation. We provide a novel framework that integrates energy and environmental life cycle assessment techniques so that dissimilar impacts can be more equitably assessed. The analysis considers diffusion- and centrifuge-based nuclear technologies, as well as reservoir and run-of-river hydropower. Results suggest that these resources are substantially less efficient (in our examples, anywhere from 5 to 85%) when key externalities are included. In the conclusion, we reflect on the benefits of using a physics-based method of measuring the externalities of power generation. Highlights: Hydro and nuclear power have multiple environmental impacts beyond GHG emissions. Non-GHG externalities include water consumption, land change, waste, and safety. We quantify life cycle externalities by estimating the energy needed to mitigate them. EF (efficiency factors) [MWhe /MWhth ] decrease when mitigation energy is included. EFs fall by 5–85% when impacts are internalized, depending on technology type.